Streptococcus pneumoniae serotype 19A in hospitalized children with invasive pneumococcal disease after the introduction of conjugated vaccines in Lima, Peru - Theresa J. Ochoa; Olguita Del Águila; Isabel Reyes; Eduardo Chaparro; María E. Castillo; Francisco Campos; Andrés Saenz; Roger Hernandez; Alessandra Luna-Muschi; Franco Castillo-Tokumori; Andrea E. Montero; Brayan E. Gonzales; et al. (Elsevier, 2024)
Background: The Pneumococcal conjugate vaccine (PCV) has decreased cases of invasive pneumococcal disease (IPD) worldwide. However, the impact of PCVs introduction may be affected by the serotype distribution in a specific context. Methods: Cross-sectional multicenter passive surveillance study of IPD cases in pediatric patients hospitalized in Lima, Peru between 2016 and 2019 (after PCV13 introduction) to determine the serotype distribution and antimicrobial resistance of Streptococcus pneumoniae. Serotyping was performed by a sequential multiplex PCR and confirmed by whole genome sequencing. Results: Eighty-five S. pneumoniae isolates were recovered (4.07/100,000 among children <60 months of age). Serotype 19A was the most common (49.4%). Children infected with serotype 19A in comparison with children infected with other serotypes were younger, had a lower rate of meningitis and higher rates of pneumonia, complicated pneumonia and antimicrobial resistance; 28.6% of patients with serotype 19A have received at least one dose of PCV13 vs. 62.8% of patients with other serotypes. Using MIC-breakpoints, 81.2% (56/69) of non-meningitis strains and 31.2% (5/16) of meningitis strains were susceptible to penicillin; 18.8% (3/16) of meningitis strains had intermediate resistance to ceftriaxone. Resistance to azithromycin was 78.8% (67/85). Serotype 19A frequency increased over time in the same study population, from 4.2% (4/96) in 2006-2008, to 8.6% (5/58) in 2009-2011, to 49.4% (42/85) in the current study (2016-2019) (p < 0.001). Conclusions: After PCV13 introduction in Peru, serotype 19A remains the most prevalent; however, the vaccination coverage is still not optimal. Therefore, additonal surveillance studies are needed to determine the remaining IPD burden.